Rac3 Regulates Cell Invasion, Migration and EMT in Lung Adenocarcinoma through p38 MAPK Pathway - Zhang, Chenlei (J Cancer, 2017)
Background: The role of Rac3 in cell proliferation in lung adenocarcinoma has been tackled in our previous study. However, the role of Rac3 in cell invasion and migration of lung adenocarcinoma is still not clear. Methods: The expression of Rac3 in lung adenocarcinoma specimens and paired noncancerous normal tissues were evaluated by immunohistochemistry. Lentivirus-mediated RNA interference (RNAi) was employed to silence Rac3 in lung adenocarcinoma cell lines A549 and H1299. A p38 MAPK inhibitor (LY2228820) was employed to inhibit activity of p38 MAPK pathway. Cell invasion and migration in vitro were examined by invasion and migration assays, respectively. PathScan(® )intracellular signaling array kit and western blot were employed in mechanism investigation. Results: Rac3 expression was frequently higher in lung adenocarcinoma than paired noncancerous normal tissues. Rac3 expression was an independent risk factor for lymphonode metastasis, and was associated with worse survival outcome. Silencing of Rac3 inhibited cell invasion and cell migration in lung adenocarcinoma cell lines. Knockdown of Rac3 decreased activity of p38 MAPK pathway. LY2228820, which was an important p38 MAPK inhibitor, inhibited Rac3-induced cell invasion and migration of lung adenocarcinoma. E-cadherin expression was increased and vimentin expression was decreased after silencing of Rac3 or following the treatment of LY2228820. Conclusions: Our findings suggest that Rac3 regulates cell invasion, migration and EMT via p38 MAPK pathway. Rac3 may be a potential biomarker of invasion and metastasis for lung adenocarcinoma, and knockdown of Rac3 may potentially serve as a promising therapeutic target for lung adenocarcinoma.